Tribulations of the Last Mile: Sides from a Regional Program - Del Rio Vilas, Victor J.; Freire de Carvalho, Mary J.; Vigilato, Marco A. N.; Rocha, Felipe; Vokaty, Alexandra; Pompei, Julio A.; Molina Flores, Baldomero; Fenelon, Natael; Cosivi, Ottorino (Frontiers in Veterinary Science, 2017)
In Latin American and Caribbean (LAC) countries, the number of cases of dog-mediated human rabies is at its lowest since the onset of the Regional Programme for Rabies Elimination in 1983, a commitment from LAC countries to eliminate dog-mediated rabies coordinated by the Pan American Health Organization (PAHO). Despite minor setbacks, the decline in the number of human cases has been constant since 1983. While many LAC countries have significantly reduced rabies to a level where it is no longer of significant public health concern, elimination has proven elusive and pockets of the disease remain across the Region. In the 33-year period since 1983 the Region has set and committed to four dates for elimination (1990, 2000, 2012, and 2015). In this paper, we ponder on the multiple causes behind the elusive goal of rabies elimination, such as blanket regional goals oblivious to the large heterogeneity in national rabies capacities. Looking ahead to the elimination of dog mediated rabies in the Region, now established for 2022, we also review the many challenges and questions that the Region faces in the last mile of the epidemic. Given the advanced position of the Americas in the race towards elimination, our considerations could provide valuable knowledge to other regions pursuing elimination goals.